(untitled) (Scientific journal of the Fergana State University, 2024)
The use of innovative technologies in the process of teaching a foreign language in the modern education system remains to be the demand of the time. Today’s pedagogues are required to orga nize lessons using modern pedagogical technologies and to have in-depth knowledge of computer technologies. This article offers websites that can be used in the process of working with text in English and analyzes the methodology of using them in the lesson.